ZmCCA1a on Chromosome 10 of Maize Delays Flowering of Arabidopsis thaliana - Yong Shi; Xiyong Zhao; Sha Guo; Shifeng Dong; Yanpeng Wen; Zanping Han; Weihuan Jin; Yanhui Chen (Frontiers in Plant Science, 2020)
Maize (Zea mays) is a major cereal crop that originated at low latitudes, and thus photoperiod sensitivity is an important barrier to the use of tropical/subtropical germplasm in temperate regions. However, studies of the mechanisms underlying circadian regulation in maize are at an early stage. In this study we cloned ZmCCA1a on chromosome 10 of maize by map-based cloning. The gene is homologous to the Myb transcription factor genes AtCCA1/AtLHY in Arabidopsis thaliana; the deduced Myb domain of ZmCCA1a showed high similarity with that of AtCCA1/AtLHY and ZmCCA1b. Transiently or constitutively expressed ZmCCA1a-YFPs were localized to nuclei of Arabidopsis mesophyll protoplasts, agroinfiltrated tobacco leaves, and leaf and root cells of transgenic seedlings of Arabidopsis thaliana. Unlike AtCCA1/AtLHY, ZmCCA1a did not form homodimers nor interact with ZmCCA1b. Transcripts of ZmCCA1a showed circadian rhythm with peak expression around sunrise in maize inbred lines CML288 (photoperiod sensitive) and Huangzao 4 (HZ4; photoperiod insensitive). Under short days, transcription of ZmCCA1a in CML288 and HZ4 was repressed compared with that under long days, whereas the effect of photoperiod on ZmCCA1a expression was moderate in HZ4. In ZmCCA1a-overexpressing A. thaliana (ZmCCA1a-ox) lines, the circadian rhythm was disrupted under constant light and flowering was delayed under long days, but the hypocotyl length was not affected. In addition, expression of endogenous AtCCA1/AtLHY and the downstream genes AtGI, AtCO, and AtFt was repressed in ZmCCA1a-ox seedlings. The present results suggest that the function of ZmCCA1a is similar, at least in part, to that of AtCCA1/AtLHY and ZmCCA1b, implying that ZmCCA1a is likely to be an important component of the circadian clock pathway in maize.